Safety and Feasibility of Including the Fracture Level in the Fixation Construct for Traumatic Vertebral Fractures - Elkholy, Hany; El Nagar, Mohamed Ahmed; Elnoamany, Nour; Elsisi, Alaa; Aborahma, Hisham (Indian Journal of Neurotrauma, 2025)
Management of spinal injuries is continuously evolving and the main surgical aim is to restore the spine integrity. Performing short-segment fixation (SSF) or long-segment fixation (LSF) is still under debate and there is limited data concerning the safety and value of including the fracture segment in the fixation construct.A retrospective observational series included 69 patients ≥ 18 years who suffered unstable thoracic, lumbar, or thoracolumbar vertebral fractures that were treated with pedicle screws fixation from January 2021 to January 2024. The aim was to evaluate the safety and value of including the fracture level in the fixation construct; preoperative clinical and radiographic parameters (visual analog scale [VAS], Oswestry Disability Index [ODI], anterior vertebral body [AVB] height) were compared with the postoperative ones at discharge and after 12 months.The mean age was 32.61 ± 9.11 years. Males constituted 55.1%. Back pain was the predominant clinical presentation followed by lower limb weakness, 24.6%. L1 was the most commonly affected level (34.8%) followed by D12 (33.3%). SSF was done in 65.2% and 34.8% were operated with LSF. Patients operated with SSF showed less intraoperative blood loss and shorter operative duration. After 12 months, there was significant improvement in regards to VAS score, Cobb angle, ODI score, and AVB height (p < 0.001).While treating vertebral fractures, provided that the pedicle walls are intact, incorporation of the fractured vertebra in the fixation construct can offer a safe, feasible, and effective method for intraoperative fracture reduction and correction of sagittal deformity, in addition to good stiffness, strong pullout strength, and maintained correction over time.
Keywords: vertebral fractures; short-segment fixation; long-segment fixation; transpedicular screws; fracture level